Tourism in Urban Intervention Processes: the Case of Little Africa (RJ) - Anízio Rios, Débora; Silva Alves de Oliveira, Maria Amália (Anais Brasileiros de Estudos Turísticos, 2022)
The article promotes an analysis of the ten years of implementation of the Porto Maravilha [Marvelous Port] project in the port area of the city of Rio de Janeiro (Brazil). Returning to previous projects, the article describes the territory in question from different models of urban intervention, presenting the space in question as a target of disputes. In this scenario, subterranean memories and narratives of resistance provide possibilities for reflection about the social function of tourism, since assets recognized as symbols of the African diaspora in the region, such as the archaeological site of Cais do Valongo, challenge silencing and tension social structures towards a new collective consciousness about heritage, ancestry and Brazilian identity.